Assessing the Senior High School Work Immersion with Partner Industries: Basis for Supervisory Work Plan - Irene Macalintal; Criselda De Chavez (JPAIR, 2020)
The researchers wanted to assess the preparedness of the Grade 12 students for work immersion in terms of punctuality, interpersonal relationship, efficiency, productivity, and safety. The descriptive method of research was used in this study. An online survey was conducted from 48 student respondents from Calamba City Senior High School who graduated during the school year 2017-2018 and 2018-2019 under the STEM strand. The results showed that students were prepared for work immersion in terms of punctuality, interpersonal relationship, and safety measures, as indicated in their responses. They were not as prepared as the first three mentioned indicators when it comes to efficiency and productivity, as revealed in the responses. Problems like the Attitude of superiors towards students, schedule of work, unapproachable co-workers, and tedious work were encountered. Based on the findings, the following conclusions were made: Grade 12 students were prepared for work immersion, and they need more activities to develop themselves to become efficient workers. There were problems encountered by Senior High School students during work immersion with partner industries that need to be addressed in school for them to adapt when they are in the actual workplace easily.